2022
DOI: 10.1021/acsomega.2c03600
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazole Derivatives against Carbonic Anhydrase: Synthesis, Molecular Docking, MD Simulations, and Free Energy Calculations Coupled with In Vitro Studies

Abstract: Heterocyclic compounds with a five-membered ring as a core, particularly those containing more than one heteroatom, have a wide spectrum of biological functions, especially in enzyme inhibition. In this study, we present the synthesis of five-membered heterocyclic isoxazole derivatives via sonication of ethyl butyrylacetate with aromatic aldehyde in the presence of a SnII-Mont K10 catalyst. The synthesized compounds were characterized using sophisticated spectroscopic methods. In vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…20d (R = 2-Ffuorophenyl) showed excellent inhibition against hCA IX with K i values of 22 nM whereas 24e showed better inhibition against hCA XII with K i values of 8.7 nM [23] (Scheme 3). Newly synthesized compounds were also subjected to in silico studies by using Gaussian 09 with the B3LYP/6-31G basis set to optimize geometry and it was observed that compounds 28b and 28c with high binding energy of −15.07 and −13.95 kcal/mol proved to be potent inhibitors against CA IX [24] (Scheme 4). Newly synthesized compounds were evaluated for their inhibitory activity against cytosolic hCA II by taking zonisamide as a standard drug and it was observed that 34h, X = COOCH 3 34i (R 1 = R 2 = H, R 3 = OH, X = CN), 34j (R 1 = R 2 = H, R 3 = OH, X = COOC 2 H 5 ) with IC 50 values of 4.55 ± 0.22, 4.91 ± 1.13, and 7.78 ± 0.08 µM, respectively, due to the presence of electron-donating OH group.…”
Section: S C H E M E 1 Synthesis Of 13(a-d)mentioning
confidence: 99%
See 2 more Smart Citations
“…20d (R = 2-Ffuorophenyl) showed excellent inhibition against hCA IX with K i values of 22 nM whereas 24e showed better inhibition against hCA XII with K i values of 8.7 nM [23] (Scheme 3). Newly synthesized compounds were also subjected to in silico studies by using Gaussian 09 with the B3LYP/6-31G basis set to optimize geometry and it was observed that compounds 28b and 28c with high binding energy of −15.07 and −13.95 kcal/mol proved to be potent inhibitors against CA IX [24] (Scheme 4). Newly synthesized compounds were evaluated for their inhibitory activity against cytosolic hCA II by taking zonisamide as a standard drug and it was observed that 34h, X = COOCH 3 34i (R 1 = R 2 = H, R 3 = OH, X = CN), 34j (R 1 = R 2 = H, R 3 = OH, X = COOC 2 H 5 ) with IC 50 values of 4.55 ± 0.22, 4.91 ± 1.13, and 7.78 ± 0.08 µM, respectively, due to the presence of electron-donating OH group.…”
Section: S C H E M E 1 Synthesis Of 13(a-d)mentioning
confidence: 99%
“…Newly synthesized compounds were also subjected to in silico studies by using Gaussian 09 with the B3LYP/6‐31G basis set to optimize geometry and it was observed that compounds 28b and 28c with high binding energy of −15.07 and −13.95 kcal/mol proved to be potent inhibitors against CA IX [ 24 ] (Scheme 4).…”
Section: Chemistry Of Heterocycles As Ca Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics is a computer simulation method for evaluating the stability of a small molecule binding to a protein target (Guterres and Im 2020). Several previous studies have reported on ligand-protein complex formations by validating their results using molecular docking and MD simulations, to support their in vitro results (Elkaeed et al 2022, Saleem et al 2022, Deswal et al 2023, Nassar et al 2023.…”
Section: Simulation Of Fucoxanthin On Ace2-spike Protein and M Promentioning
confidence: 99%
“…Their structural features make them essential building blocks in organic synthesis, contributing to the creation of bioactive compounds. Isoxazoles are also recognized for their antimicrobial [13,14], anticancer [15,16], anticholinesterase [17] and diuretic properties [18].…”
Section: Introductionmentioning
confidence: 99%